In vitro sensitivity of Fusarium graminearum isolates to fungicides - Avozani,Aveline (2014)
Head blight of wheat is a disease of global importance. In Brazil, it can cause damage of up to 27%. As resistant cultivars are not available yet, short-term disease control relies on the use of fungicides. The first step to reach effective management is to identify potent fungicides. In vitro experiments were conducted to determine the inhibitory concentration 50% (IC50) for mycelial growth or conidial germination, according to the chemical group of fungicides, of five Fusarium graminearum isolates of different origins. The following demethylation inhibitor (DMI) fungicides were tested: epoxiconazole, cyproconazole, metconazole, prochloraz, protioconazole and tebuconazole. In addition, azoxystrobin, kresoxim-methyl, pyraclostrobin and trifloxystrobin were included in the study, representing Quinone outside inhibitor fungicides (QoI), as well as a tubulin synthesis inhibitor, carbendazim and two ready mixtures, trifloxystrobin + tebuconazole or trifloxistrobin + prothioconazole. DMI's showed lower IC50 values compared to the QoI's. For the five tested isolates, in the overall mean, IC50 considering mycelial growth ranged for DMI's from 0.01 mg/L (metconazole, prochloraz and prothioconazole) to 0.12 mg/L (cyproconazole) and considering conidial germination for QoI's from 0.21 mg/L (azoxystrobin) to 1.33 mg/L (trifloxystrobin). The IC50 for carbendazim was 0.07 mg/L. All tested isolates can be considered sensitive to the studied DMI's, although certain differences in sensitivity could be detected between the isolates originating from one same state.